Exploration of Adolescent Resilience in The Slopes of Mount Merapi - Purwadi, Purwadi; Prasetya, Arif Budi; Prasetiawan, Hardi; Elsanadia, Oktolita (Universitas Ahmad Dahlan, 2024)
This study aims to determine the level of resilience based on ethnicity and family conditions. The respondents were students from various levels of education from vocational high school, high school and junior high school education levels in the Mount Merapi slope area. The instrument used is the Connor-Davidson Resilience Scale (CD-RISC) Short version-10 items that have been adapted with a reliability value of 0.801. The data analysis used was Kruskal Wallis non-parametric statistics as a test of tribal differences and family conditions. The results showed that there were no significant differences based on ethnicity and family conditions. The results of this study can be considered in designing guidance and counseling programs and services.